Базисна модель формування витрат життєвого циклу об’єктів нерухомості - Ніколаєва, Т. В. (Ways to Improve Construction Efficiency, 2014)
The investment process during the facility life cycle from preparation until demolishing is modeled. The appropriate maintenance and capital expenses are structured and presented as current and capital cash flows. The centers of cost management and normal expenses proportions are formed. The influence of discount rate and inflation on the maintenance cost is analyzed.